Electrolyte additive and rechargeable battery comprising same
By adding metal/metal ions as in-situ doping sources to the electrolyte of a rechargeable manganese-zeb battery, the problem of poor cycle stability of manganese-based cathode batteries is solved, and long-term maintenance of battery capacity and stability of electrode structure is achieved.
Patent Information
- Application Number
- CN202411120353.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-15
- Filing Date
- 2024-08-15
- Publication Date
- 2025-02-21
AI Technical Summary
The cycle stability of rechargeable manganese-zeb batteries is poor, especially under the demand for high capacity utilization, resulting in a decrease in battery capacity and an increase in electrode resistance.
A small amount of metal/metal ions, such as Ti4+, is added to the electrolyte, as an in-situ doping source, and a metal/metal quasi-doped manganese-based cathode is formed during the charging/discharging process to inhibit the formation of the ZnxMnyO phase.
The circulation performance of manganese-based cathode batteries is significantly improved, the cycle life of the battery is extended, the utilization rate of the capacity is maintained, and the electrode structure is stabilized.
Smart Images

Figure CN119495835A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to an electrolyte additive for a rechargeable manganese-zinc battery. Background Art
[0002] Rechargeable aqueous manganese zinc batteries are promising candidates to replace commercial lead-acid batteries due to their intrinsic safety, low cost, low toxicity, and moderate energy density. However, poor cycling stability is a major obstacle to the practical application of rechargeable manganese zinc batteries, especially for batteries with high capacity utilization, such as >200 mAh g -1 Specifically, during cycling, the MnO2 cathode will undergo an irreversible phase transformation into electrochemically inert phases such as ZnMn2O4 and ZnMn3O7. These Zn-containing phases are stable, and Zn ions are hardly released. As a result, the active cathode material is gradually consumed, resulting in a decrease in capacity during cycling.
[0003] In conventional manganese-zinc batteries, different types of MnO2 polymorphs are usually used as cathodes and Zn foil is used as anodes. Aqueous 1M ZnSO4+0.1M MnSO4 liquid can be used as the electrolyte. Figure 1 This typical configuration is illustrated in .
[0004] This aqueous system can achieve approximately 300 mAh g -1 During discharge, MnO2 undergoes proton insertion reaction (Equation 1), as well as MnO2 dissolution (Equation 2):
[0005] MnO2+H + +e - →HMnO2(s)(Eq. 1)
[0006] MnO2+4H + +2e - →Mn 2+ (l) + 2H2O (Equation 2)
[0007] During the charging process, protons are released and MnO2 deposition occurs as a reversible reaction of Eq. 1 and Eq. 2. However, 2+ A side reaction usually occurs when doped into the MnO2 cathode (Eq. 3):
[0008] 2Mn 2+ +Zn 2+ +8OH-→ZnMn2O4+4H2O+2e - (Equation 3)
[0009] In addition to ZnMn2O4, we can sometimes find ZnMn3O7 phase. The phase change is not obvious in a short cycle life, but it is found that these Zn x Mn y O phases will accumulate. These phases are electrochemically inactive and thus gradually consume the active MnO2 cathode, resulting in a decrease in battery capacity ( Figure 2 ). At the same time, these phases will increase the electrode resistance and hinder ion transport.
[0010] Additives are often added to the electrolytes of other battery systems (such as lithium-ion batteries, Li-S batteries, and Li metal batteries) to improve battery performance (such as cycle performance). Additives are usually organic-based, such as solvents, polymers, or chemicals containing P, F, B, and S. Depending on the additive, the mode of action of the additive is also different, such as increasing the electrochemical stability window of the electrolyte to inhibit electrolyte decomposition, inducing the formation of a stable surface film to prevent further reaction, inhibiting side reactions between the electrolyte and the active material, inhibiting dendrite formation on the metal surface and improving metal deposition, inhibiting corrosion of the current collector, promoting the wetting of the electrolyte, reducing viscosity, and increasing the ionic conductivity of the electrolyte.
[0011] Some previous studies have improved the cycling performance of rechargeable manganese-zinc batteries by preventing the phase transformation of MnO2. For example, an ion exchange resin was developed as a Zn-repellent 2+ The diaphragm does not contain Zn 2+ catholyte to avoid the MnO2 cathode from the anode side with Zn 2+ However, this design requires a complex setup that reduces the actual energy density of the battery. Another study showed that the cycled cathode could be cleaned in acid to remove the capping Zn x Mn y O, and then reassemble with new electrolyte to restore the electrode capacity. However, this method is not practical in actual applications. Some previous studies designed nanoscale MnO2 structures with improved stability, however, the synthesis process is costly. In addition, these studies directly used doped MnO2 as the cathode material. This pre-prepared doped MnO2 may be gradually replaced by newly deposited undoped MnO2 during the charge / discharge process and thus fail to provide long-term functionality.
[0012] Therefore, there is a need to improve the cycling performance of rechargeable manganese-based cathode batteries. There is also a need to develop additives for improving the performance of manganese-based cathode batteries. Summary of the invention
[0013] One embodiment of the present invention relates to an electrolyte for a battery comprising a manganese-based cathode, the electrolyte further comprising a compound of formula Mn+ A metal / metalloid ion wherein M represents a metal / metalloid and wherein n is from about 2 to about 4.
[0014] One embodiment of the present invention is directed to a battery having a manganese-based cathode comprising an electrolyte as described herein; or wherein the electrolyte comprises from about 0.05% (w / v) to about 10% (w / v); or from about 0.1% (w / v) to 5% (w / v) metal / metalloid ions.
[0015] One embodiment of the present invention is directed to a method for improving the performance of a battery having a Mn-based cathode, the method comprising the electrolyte as described herein.
[0016] Without intending to be limited by theory, it is believed that the present invention provides an electrolyte that can improve the cycling performance of batteries having manganese-based cathodes. It is also believed that Mn cathode batteries containing the electrolyte according to the present invention can have long-lasting improvements in cycling performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The configuration of a conventional manganese-zinc battery is illustrated;
[0018] Figure 2 Illustrated the irreversible Zn x Mn y Formation of O phase;
[0019] Figure 3 The use of M according to the present invention is illustrated n+ The formation of M-doped MnO2 as an additive in the electrolyte and its effect on the irreversible Zn x Mn y Inhibition of O phase;
[0020] Figure 4A shows an SEM image of ball-milled commercial EMD nanoparticles used as active material in some embodiments herein;
[0021] Figure 4B shows a TEM image of ball-milled commercial EMD nanoparticles used as active material in some embodiments herein;
[0022] Figure 4C is a graph showing the BET surface area of ball-milled commercial EMD nanoparticles used as active material in some embodiments herein;
[0023] Figure 4D is a graph showing the XRD pattern of ball-milled commercial EMD nanoparticles used as active material in some embodiments herein;
[0024] Figure 4Eis a picture showing the crystal structure of ball-milled commercial EMD nanoparticles used as active material in some embodiments herein;
[0025] Figure 4F is a graph showing a SEM EDX spectrum of ball-milled commercial EMD nanoparticles used as active material in some embodiments herein;
[0026] Figure 5A shows an SEM image of a pristine EMD cathode;
[0027] Figure 5B shows an SEM image of an EMD cathode discharged to 1.20 V in the first cycle;
[0028] Figure 5C shows an SEM image of an EMD cathode discharged to 0.80 V in the first cycle;
[0029] Figure 5D shows an SEM image of an EMD cathode charged to 1.52 V in the first cycle;
[0030] Figure 5E shows an SEM image of an EMD cathode charged to 1.80 V in the first cycle;
[0031] Fig. 5F shows the voltage curve of the EMD cathode during the first cycle;
[0032] Figure 5G It shows that the Mn content in the electrolyte during the first cycle 2+ A graph of the concentration of
[0033] Figure 5H Shows Fig. 5F XRD patterns of the cathode at different discharge-charge states shown in ;
[0034] Fig.5I XRD patterns of the EMD cathode after different cycles are shown;
[0035] Figure 6 is a graph showing the charge curve of an EMD-Zn battery which was disassembled after the first discharge in a 1Zn+0.1Mn electrolyte and reassembled with a 1MZnSO4 electrolyte containing no MnSO4.
[0036] Fig. 7A The results are shown for the use of samples with and without 0.1 M Mn 2+ Graph of the first cycle voltage curve of a battery in a coin cell configuration (electrolyte volume: 200 μl) with a 1 M ZnSO4 electrolyte containing additives.
[0037] Figure 7B The results are shown for the use of samples with and without 0.1 M Mn 2+ A graph showing the first cycle voltage curve of a battery in a beaker cell configuration (electrolyte volume: 5 ml) with a 1M ZnSO4 electrolyte containing additives;
[0038] Figure 7C The results show that the use of 2+ Comparison of coulombic efficiency of batteries with 1M ZnSO4 electrolyte with additives;
[0039] Fig. 8A is a schematic illustration of an electrodeposition test configuration;
[0040] Figure 8B It shows that the capacity limit is 0.5 mAh cm in 1Zn+0.4Mn and 1Zn+0.4Mn+0.5Ti electrolytes. -2 A graph showing the voltage curve of the first cycle of the electrodeposition test when ;
[0041] Figure 8C is the SEM image of the bare CNT electrode;
[0042] Fig.8D is the SEM image of the CNT electrode after charging in 1Zn+0.4Mn electrolyte;
[0043] Fig. 8E is the SEM image of the CNT electrode after charging in 1Zn+0.4Mn+0.5Ti electrolyte;
[0044] Fig.8F This is the elemental mapping image of the CNT electrode after charging in 1Zn+0.4Mn electrolyte;
[0045] Figure 8G This is the element mapping image of the CNT electrode after charging in 1Zn+0.4Mn+0.5Ti electrolyte;
[0046] Fig.9A The charge capacity limit is 0.2 mAh cm -2 A graph showing the voltage curve of the electrodeposition test when ?
[0047] Fig. 9B The charge capacity limit is 1.0 mAh cm -2 A graph showing the voltage curve of the electrodeposition test when ?
[0048] Fig. 9C is a table showing a comparison of coulombic efficiencies in electrodeposition tests at different capacity limits;
[0049] Fig. 10AThe charge capacity is 0.5 mAh cm at a fixed area. -2 and the discharge current is 0.05 mA cm -2 Figure 2 shows the cycling performance of bare CNT / / Zn electrode using 1Zn+0.4Mn electrolyte under the condition of .
[0050] Fig. 10B The charge capacity is 0.5 mAh cm at a fixed area. -2 and the discharge current is 0.05 mA cm -2 Figure 2 shows the cycling performance of bare CNT / / Zn electrode using 1Zn+0.4Mn+0.5Ti electrolyte under the condition of ;
[0051] Fig.11A is a diagram showing XRD patterns of electrodes after charging in 1Zn+0.4Mn and 1Zn+0.4Mn+0.5Ti electrolytes in electrodeposition tests and commercial EMD;
[0052] Fig. 11B is a graph showing Raman spectra of electrodes charged in 1Zn+0.4Mn and 1Zn+0.4Mn+0.5Ti electrolytes and commercial EMD in an electrodeposition test;
[0053] Fig. 11C is a graph showing XPS Mn 2p spectra of charged electrodes and commercial EMD in 1Zn+0.4Mn and 1Zn+0.4Mn+0.5Ti electrolytes in electrodeposition tests;
[0054] Fig.11D is a graph showing Mn 3s spectra of electrodes and commercial EMD after charging in 1Zn+0.4Mn and 1Zn+0.4Mn+0.5Ti electrolytes in electrodeposition tests;
[0055] Fig.11E is a graph showing Ti 2p spectra of electrodes after charging in 1Zn+0.4Mn and 1Zn+0.4Mn+0.5Ti electrolytes in electrodeposition tests and commercial EMD;
[0056] Fig.11F is a graph showing Zn 2p spectra of electrodes and commercial EMD after charging in 1Zn+0.4Mn and 1Zn+0.4Mn+0.5Ti electrolytes in electrodeposition tests;
[0057] Fig.11G is a graph showing a DFT-calculated comparison of the formation energy (ΔE) per Zn atom incorporated into EMDs of Ti-doped and undoped Ti;
[0058] Fig.11H Shown in Fig.11GMolecular structures of EMD, Ti-doped EMD (3 / 32Ti substitution), Zn-embedded EMD, and Ti-doped EMD embedded in Zn in DFT calculations shown in ;
[0059] Fig. 12A is a graph showing the full XPS spectrum of EMD electrodeposited in 1Zn+0.4Mn electrolyte;
[0060] Fig. 12B is a graph showing the XPS full spectrum of EMD electrodeposited in 1Zn+0.4Mn+0.5Ti electrolyte;
[0061] Fig. 12C is a graph showing the full XPS spectrum of commercial EMD;
[0062] Fig.13A is a graph showing the Raman spectra of EMD electrodeposited in 1Zn+0.4Mn+0.5Ti electrolyte compared to the two most common TiO2 phases (anatase TiO2 and rutile TiO2);
[0063] Fig. 13B is a graph showing the XRD pattern of EMD electrodeposited in 1Zn+0.4Mn+0.5Ti electrolyte compared to the two most common TiO2 phases (anatase TiO2 and rutile TiO2);
[0064] Fig.14 An illustration of Ti doping in an EMD structure is shown;
[0065] Fig.15A is a graph showing CV curves of batteries using 1M ZnSO4, 1Zn+0.1Mn, and 1Zn+0.1Mn+0.5Ti electrolytes;
[0066] Fig. 15B is a graph showing the rate performance of batteries using 1M ZnSO4, 1Zn+0.1Mn, and 1Zn+0.1Mn+0.5Ti electrolytes;
[0067] Fig. 15C The results show that the battery using 1M ZnSO4, 1Zn+0.1Mn, 1Zn+0.1Mn+0.5Ti electrolyte has a high conductivity at 1200mAg. -1 Graph of cyclic stability under ;
[0068] Fig.15D is shown using Fig. 15C A graph showing the voltage curve of a battery with 1M ZnSO4 electrolyte;
[0069] Fig.15E is shown using Fig. 15CA graph showing the voltage curve of a battery with 1Zn+0.1Mn electrolyte;
[0070] Fig.15F is shown using Fig. 15C A graph showing the voltage curve of a battery with 1Zn+0.1Mn+0.5Ti electrolyte;
[0071] Figure 15G is shown at 3600mA g -1 The following is a graph showing the cycling stability of batteries using different electrolytes;
[0072] Fig.15H is shown at 4800mA g -1 The following is a graph showing the cycling stability of batteries using different electrolytes;
[0073] Fig.15I is a graph showing the comparison of the present application with previous studies in terms of cycle performance;
[0074] Fig.15J is a graph showing the comparison of the present application with previous studies in terms of energy and power density;
[0075] Fig.16 The charge-discharge curve of the KB cathode without EMD at a low current of 0.3 mA is shown;
[0076] Fig.17 The results show that at different current densities [1C = 300 mA g -1 ] Voltage curve of EMD electrode in 1Zn+0.1Mn+0.5Ti electrolyte;
[0077] Fig.18 It shows that at a current density of 900 mA g -1 Cycling performance of EMD-zinc batteries using electrolyte 1M ZnSO4+0.1M MnSO4 containing different amounts of TiOSO4 under different conditions;
[0078] Fig.19A The XRD patterns of the cathode electrode of the battery using +0.5% (w / v) TiOSO4 electrolyte after different cycles are shown;
[0079] Fig.19B Post-characterization is shown: SEM, TEM, and HRTEM images of the cathode in 1Zn+0.1Mn electrolyte after 500 cycles;
[0080] Fig.19C Post-characterization is shown: SEM, TEM, and HRTEM images of the cathode in 1Zn+0.1Mn+0.5Ti electrolyte after 500 cycles;
[0081] Fig.19D The figure shows the Mn content in the electrolyte of a battery using 1M ZnSO4 as the cycle progresses. 2+ Concentration plots;
[0082] Fig.19E It shows that the Mn content in the electrolyte of the battery using 1Zn+0.1Mn increases with the cycle. 2+ Concentration plots;
[0083] Fig.19F It shows that the Mn content in the electrolyte of the battery using 1Zn+0.1Mn+0.5Ti increases with the cycle. 2+ Concentration plots;
[0084] Figure 19G is the Nyquist plot of the EIS results of a battery using 1M ZnSO4 as it cycles;
[0085] Fig.19H is a Nyquist plot showing EIS results of a battery using 1Zn+0.1Mn as it cycles;
[0086] Fig.19I is a Nyquist plot showing EIS results of a cell using 1Zn+0.1Mn+0.5Ti over cycles;
[0087] Fig.19J is a diagram showing an equivalent circuit of an EIS result;
[0088] Figure 19K is a graph showing the comparison of Rct of cells over cycles from the EIS results.
[0089] Fig. 20 It shows that at a current density of 900 mA g -1 Cycling performance of cells using basic electrolyte and +0.5% (w / v) NiSO4 electrolyte under 40°C;
[0090] Fig.21 It shows that at a current density of 900 mA g -1 Cycling performance of cells using the base electrolyte and +0.5% (w / v) La(NO3)3 electrolyte under 10% (w / v) 2 ...
[0091] Fig. 22 shows that at 900mA g -1 Cycling performance of cells using base electrolyte, +0.5% (w / v) FeSO4 and +0.5% (w / v) Fe2(SO4)3 electrolyte at current density;
[0092] Fig.23 It shows that at a current density of 900 mA g -1Cycling performance of cells using base electrolyte and +0.5% (w / v) H3BO3 electrolyte under 40°C;
[0093] Fig.24 It shows that at a current density of 900 mA g -1 Cycling performance of cells using the base electrolyte and +0.5% (w / v) MgSO4 electrolyte under 40°C;
[0094] Fig.25 It shows that at a current density of 900 mA g -1 Cycling performance of Mn2O3-zinc batteries using 1M ZnSO4+0.1MMnSO4 electrolyte with or without TiOSO4;
[0095] Fig.26 It shows that at a current density of 900 mA g -1 The cycling performance of a delta-MnO2-zinc battery using a 1M ZnSO4+0.1M MnSO4 electrolyte with or without TiOSO4 under 4% t / cm2 conditions; and
[0096] Fig. 27 It shows that at a current density of 900 mA g -1 Cycling performance of β-MnO2-zinc battery using 1M ZnSO4+0.1M MnSO4 electrolyte with or without TiOSO4.
[0097] The figures herein are for illustration purposes only and are not necessarily drawn to scale. DETAILED DESCRIPTION
[0098] Unless otherwise expressly specified, all tests herein are conducted under standard conditions, including room temperature and test temperature of 25°C, sea level (1 atm.) pressure, pH 3.5-6, and all measurements are in metric units. In addition, all percentages, ratios, etc. herein are by weight unless otherwise expressly indicated. It should be understood that, unless otherwise expressly stated, the material compounds, chemicals, etc. described herein are generally commercial products and / or industry standards that can be obtained from various suppliers around the world.
[0099] This application describes an electrolyte containing a small amount of metal / metalloid ion additives for rechargeable aqueous batteries with a manganese-based cathode to improve the cycling stability.
[0100] One embodiment of the present application relates to an electrolyte for a battery including a manganese-based cathode, the electrolyte further comprising a compound of formula M n+ A metal / metalloid ion of wherein M represents a metal / metalloid and n is from about 2 to about 4.
[0101] Without wishing to be bound by theory, it is believed that a small amount of metal / metalloid ions contained in the electrolyte can serve as an in-situ doping source to form a metal / metalloid doped manganese-based cathode (such as a doped MnO2 cathode) during the charge / discharge process, which can stabilize the cathode structure and inhibit the Zn x Mn y The formation of O phase, such as Figure 3 In the case where the electrolyte contains zinc (e.g., Zn 2+ ), regardless of the anode material, the electrolyte according to the present application can obtain the above benefits.
[0102] In previous studies, they used pre-prepared doped MnO2 as the cathode, which may be gradually replaced by newly deposited undoped MnO2 due to the continuous dissolution / deposition of MnO2 during the charge / discharge process. This may lead to the inhibition of Zn x Mn y O phase formation function loss. In contrast, it is believed that the present application solves the problem in a different way, by using additives in the electrolyte, in situ doping manganese-based cathode materials (such as MnO2) to stabilize the active material during charging and discharging. Therefore, it is believed that compared with the pre-prepared doped MnO2, the described in-situ doping process can provide a doped cathode with a longer-lasting function of improving cycle performance. The technical problem can be solved by simply adding metal / metalloid ions, for example, in the form of their salts to the electrolyte. That is, we do not need to change the mass production process of MnO2. In addition, it is believed that in-situ doping can allow more dopants on the surface of the material, which is more effective than bulk doping in the synthesis process. In addition, the present application can be applied not only to commercial electrolytic manganese dioxide (EMD), but also to different MnO2 polymorphic structures.
[0103] At the same time, it is believed that there are currently no publications or patents proposing electrolyte additives similar to the present application to inhibit the MnO2 phase transformation and improve the cycle performance of rechargeable manganese-zinc batteries.
[0104] In some embodiments, the metal / metalloid ions contained in the electrolyte according to the present application are selected from the group consisting of: Ti 4+ 、TiO 2+ 、Ni 2+ , Fe 2+ , Fe 3+ ,La 3+ 、Zr 4+ 、ZrO 2+ Sn 2+ 、Bi 3+ 、V 4+ 、V 3+ 、V 2+ 、Al 3+, Sb 3+ Mg 2+ , Ca 2+ , B 3+ , and combinations thereof; or combinations thereof; or Ti 4+ 、TiO 2+ 、Ni 2+ ,La 3+ , Fe 2+ , Fe 3+ In some embodiments, the metal / metalloid ions contained in the electrolyte according to the present application are selected from Ti 4+ 、TiO 2+ As shown in the examples herein, Ti 4+ and TiO 2+ The best cycling performance can be achieved. Without wishing to be bound by theory, it is believed that ions from the same group of elements, such as Zr and Ti, Ca and Mg, Al and B, and ions from adjacent groups of elements, such as V and Ti, will achieve similar effects in this application.
[0105] In some embodiments, the electrolyte according to the present application comprises metal ions, and the metal ions may be transition metal ions selected from the following groups: Ti ions (such as Ti 4+ 、TiO 2+ ), Ni ions (such as Ni 2+ ), Fe ions (such as Fe 2+ , Fe 3+ ), La ions (such as La 3+ ), Zr ions (such as Zr 4+ 、ZrO 2+ ), V ions (such as V 4+ 、V 3+ 、V 2+ ) and their combinations.
[0106] In some embodiments, the electrolyte according to the present application comprises a semi-metal ion selected from the following group: Sb ions (such as Sb 3+ ), B ions (such as B 3+ ) and their combinations.
[0107] In some embodiments, the electrolyte according to the present application comprises metal ions, and the metal ions may be alkaline earth metals or other metal ions selected from the following groups: Sn ions (Sn 2+ ), Bi ions (Bi 3+ ), Al ions (Al 3+ ), Mg ions (Mg 2+ ), Ca ions (Ca 2+ ) and their combinations.
[0108] Typically, for manganese-zinc batteries, MnSO4 is added to the electrolyte to reduce the dissolution of Mn from the MnO2 active material into the electrolyte. The function of adding MnSO4 is different from the addition of metal / metalloid salts used in this application, which is used to form in-situ doping of active materials. Since no other metal / metalloid elements in the Mn-containing active material dissolve into the electrolyte, it is believed that those skilled in the art cannot predict that the addition of metal / metalloid salts (except MnSO4) such as Ti, Ni, etc. provided in this application will be an effective solution to improve the cycle performance of Mn-based cathode batteries.
[0109] As far as the inventors know, there is no report on the addition of transition metal / metalloid salt additives into the electrolyte and electrochemically doping them into active materials to improve cycle performance. In fact, the presence of transition metal ions in the electrolyte is harmful to most batteries (such as lithium-ion batteries) because they can be transported and deposited on the anode, thereby poisoning the anode and causing the battery performance to decrease. Therefore, those skilled in the art would not expect to add transition metal / metalloid salts to the electrolyte because they believe that addition would reduce the performance of the battery.
[0110] In some embodiments, the electrolyte according to the present application comprises metal / metalloid ions in the form of salts. For example, the electrolyte may comprise any salt selected from the group consisting of TiOSO4, NiSO4, La(NO3)3, Fe2(SO4)3, FeSO4, H3BO3, MgSO4, and combinations thereof. In some embodiments, the electrolyte may comprise TiOSO4.
[0111] In some embodiments, the metal / metalloid ion M in the electrolyte according to the present application is n+ The content range is about 0.1% (w / v) to about 5% (w / v). The percentage content of the additive described herein is defined as the weight of the salt of the ion in 100 ml of the basic electrolyte. For example, 5% (w / v) TiOSO4 means that 0.5g TiOSO4 is added to 100ml of the basic electrolyte.
[0112] In some embodiments, the metal / metalloid ion M in the electrolyte according to the present application is n+ The content of metal / metalloid ion M in the electrolyte according to the present application is about 0.1% (w / v), about 0.2% (w / v), about 0.3% (w / v), about 0.4% (w / v), about 0.5% (w / v), about 1% (w / v), about 2% (w / v), about 3% (w / v), about 4% (w / v), about 5% (w / v). n+The content range is about 0.1% (w / v) to about 0.5% (w / v), about 0.3% (w / v) to about 1% (w / v), about 0.4% (w / v) to about 2% (w / v), about 3% (w / v) to about 4% (w / v), or about 3% (w / v) to about 5% (w / v).
[0113] In some embodiments, metal / metalloid ions are used as in-situ doping sources to form metal / metalloid doped manganese-based cathodes during the charge / discharge process of the battery. Without intending to be bound by theory, it is believed that the metal / metalloid ions used herein can enter the manganese cathode material during the charge / discharge process and inhibit the incorporation of Zn ions.
[0114] One embodiment of the present application relates to a battery having a Mn-based cathode, comprising an electrolyte as described herein; or wherein the electrolyte comprises about 0.05% (w / v) to about 10% (w / v); or about 0.1% (w / v) to 5% (w / v) of metal / metalloid ions.
[0115] In some embodiments, the manganese-based cathode comprises a cathode material selected from the group consisting of MnO2, MnO, Mn3O4, Mn2O3, MnOOH, and combinations thereof. Without wishing to be bound by theory, it is believed that the inactive Zn x Mn y The O phase may be formed due to the reaction between Zn and Mn oxides. In addition, it is believed that during the charge / discharge process of this system, the Mn oxide as the cathode will eventually be converted into MnO2, so the reaction thereafter will be the same. During the charge / discharge process of the battery, the metal / metalloid ion additives in the electrolyte will enter the cathode material, thereby forming doped MnO2 and preventing the inactive Zn on the cathode from x Mn y Formation of O phase. In some embodiments, MnO2 is attractive because of its environmental friendliness, availability in large quantities, and high capacity.
[0116] In some embodiments, in the battery according to the present application, the cathode material is MnO 2. MnO 2 has been commercially produced on a large scale and is therefore easily available.
[0117] In some embodiments, in the battery according to the present application, the cathode material MnO2 has different polymorphs selected from the group consisting of α, β, γ, δ, λ, Ramsdellite and electrolytic manganese dioxide (EMD) structures. In some embodiments, the cathode material MnO2 has an EMD structure. Without intending to be bound by theory, it is believed that the EMD structure has a disordered structure, which allows for higher capacity and easier reaction between the cathode and the metal / metalloid ions for doping.
[0118] In some embodiments, in the battery according to the present application, the manganese-based cathode comprises M n+ doping structure, which prevents the manganese-based cathode from transforming into an electrochemically inert phase.
[0119] In some embodiments, the battery according to the present application may include an anode. The anode comprises a material selected from the group consisting of zinc, zinc alloys (such as brass) and combinations thereof. In some embodiments, the battery according to the present application may be an anode-free battery, wherein zinc is deposited on, for example, Cu or carbon.
[0120] In some embodiments, the battery is an aqueous zinc ion battery. It is believed that aqueous rechargeable Zn ion batteries (ARZIBs) are promising for grid-scale energy storage applications due to their abundant Zn sources, intrinsic safety, and low cost.
[0121] In some embodiments, the battery is an aqueous zinc ion battery using a manganese-based material as a cathode, for example, the battery may include a MnO2-Zn system. It is believed that the electrolyte additive according to the present application can improve the stability of MnO2, thereby preventing capacity decay during cycling and improving the electrochemical performance of aqueous MnO2-Zn batteries.
[0122] In this application, we developed novel and facile electrolyte additives to suppress the phase transformation that usually occurs in conventional rechargeable manganese-zinc batteries and also stabilize the cathode structure. Specifically, we developed different metal / metalloid ions as electrolyte additives, which can enter the manganese cathode material during the charge / discharge process and suppress the incorporation of Zn ions. As a result, the cycling performance can be significantly improved.
[0123] One embodiment of the present application relates to a method for improving the performance of a battery having a Mn-based cathode, the method comprising the electrolyte as described above.
[0124] The electrolyte and battery described above are suitable for use in this embodiment.
[0125] As described herein, the electrolyte additives comprising metal / metalloid ions herein can form metal / metalloid doped manganese-based cathodes by in-situ doping when the battery is charged and discharged. Without intending to be bound by theory, it is believed that the addition of metal / metalloid salts (such as TiOSO4) as a simple electrolyte additive suppresses the appearance of inactive phases by forming Ti-doped MnO2 during the cycling process, thereby improving the cycling stability of the electrode.
[0126] The formation of inactive phases upon cycling has been reported to be one of the reasons for the poor electrochemical reversibility of different MnO2-based polymorphs. So far, many strategies have been proposed to overcome this problem, such as surface coatings, designing different MnO2 morphologies and crystal structures, introducing vacancies and dopants, and electrode additives. However, most of the reported studies were only able to demonstrate stable cycling performance at high current rates and low capacity utilization (e.g., <150 mAh g after 1000 cycles). -1 ), because in each cycle, MnO2-Mn 2+ The presence of the dissolution-deposition reaction inevitably counteracts the effect of the originally designed MnO2 structure. For practical applications, it is desirable to find an alternative method to suppress the formation of the inactive phase in order to maintain over 200 mAh g for extended cycle times. -1 High capacity utilization.
[0127] In this application, we first systematically investigate the charge storage mechanism and inactive phase formation process of electrolytic manganese dioxide (EMD). Specifically, we observe that proton insertion / extraction and MnO2 dissolution-deposition reactions occur simultaneously to contribute to the capacity. Meanwhile, inactive ZnMn2O4 and ZnMn3O7 phases gradually emerge in the electrode upon cycling. These new Zn-containing phases are the result of the Mn removal during the charge process. 2+ and Zn 2+ as verified by EMD electrodeposition tests on cathode-free carbon nanotube (CNT) electrodes.
[0128] The present application further demonstrates that the addition of TiOSO4 as an electrolyte additive is an effective method to suppress the formation of Zn-containing phases by in-situ formation of Ti-doped EMD during cycling, significantly improving the cyclability of MnO2. Experimental data show that Ti-doped EMD can be favorably formed compared to Zn-Mn-O phases, and the stability is confirmed by density functional theory (DFT) calculations. Using 0.5% (w / v) TiOSO4 additive, MnO2-Zn batteries have a high cycling performance at about 1200 mA g / min. -1 After about 1500 cycles at a current of about 230 mAh g -1 The stable capacity corresponds to a charge-discharge time of about 12 minutes (5C rate). Stable cycling is achieved even at higher current rates, at about 3600mAg -1 After about 6000 cycles at about 15C, the capacity is about 113 mAh g -1 , and at about 4800mA g -1 After about 10,000 cycles at about 30C, the capacity is about 92 mAh g -1The excellent cyclability of MnO2 is due to the improved stability of EMD with TiOSO4 additive, as confirmed by X-ray diffraction (XRD) results after cycling. In addition, inductively coupled plasma (ICP) spectroscopy results show that Mn in the electrolyte 2+ The change in concentration was reversible, and electrochemical impedance spectroscopy (EIS) measurements revealed that the cell resistance of the MnO2-Zn cells remained stable with cycling when using the TiOSO4 additive.
[0129] Example
[0130] Methods and Tests
[0131] Unless otherwise stated, the following materials and conditions were used to perform the examples.
[0132] 1. Preparation of electrolyte
[0133] ZnSO4·H2O (>99.9%), MnSO4·H2O (>99%), and titanyl sulfate TiOSO4 (>29% Ti basis) were purchased from Sigma Aldrich.
[0134] The ZnSO4+MnSO4 electrolyte (basic electrolyte) was prepared by dissolving 1 M ZnSO4 and 0.1 MnSO4 in deionized water (expressed as "1Zn+0.1Mn").
[0135] Similarly, a “1Zn+0.4Mn” electrolyte was prepared by dissolving 1M ZnSO4 and 0.4M MnSO4.
[0136] The "1Zn+0.1Mn+0.5Ti" and "1Zn+0.4Mn+0.5Ti" electrolytes were prepared by dissolving 0.5% (w / v) TiOSO4 in the ZnSO4+MnSO4 electrolyte. Electrolytes with other TiOSO4 contents were prepared using the same method.
[0137] All electrolytes were prepared by stirring electrolyte salts in deionized water at room temperature for more than one hour.
[0138] 2. Battery Assembly
[0139] To prepare electrolytic manganese dioxide (EMD) electrodes, commercial EMD (Xiangtan Electrochemical Scientific Ltd.) was first ball-milled in a zirconia bowl at 200 rpm for 12 h with ethanol as a dispersant (EMD: ethanol = 1:1 by mass) to reduce the particle size. The resulting powder was vacuum dried at 60 ° C for 4 h to evaporate the ethanol.
[0140] From the SEM and TEM observations, the particle size of the ball-milled material was about 100 nm ( Figure 4A and 4B ). The BET surface area of the material is 57.3 m 2 g -1 ( Figure 4C As shown in the XRD data, the crystal structure of EMD is γ-MnO2( Figure 4D and 4E ). EDX analysis of the material showed that it contained Mn and O.
[0141] The ball-milled EMD was thoroughly mixed with Ketjen black (KB, ECP-600JD, Lion Corporation, Japan) and polyvinylidene fluoride (PVdF, solef 5130, Solvay, France) in N-methyl-2-pyrrolidone (NMP) at a ratio of 7:2:1 to make a uniform slurry, which was coated on graphite paper (GP, 50 μm thick, Chenxin Induction Equipment, China). The electrodes were punched into discs with a diameter of 16 mm and dried at 80 °C for 4 h. The typical EMD mass loading was about 1.5 mg cm -2 Coin cells were assembled as follows: using the electrodes described above as cathodes, zinc foil (Sigma Aldrich, 99.9%, 0.05 mm thick) as anodes, and glass fiber (Advantec #GD-120, Toyo Roshi Kaisha Ltd., Tokyo, Japan) as separators, and adding 200 μl of electrolyte. For other electrode materials, such as those used in Example 6 ( Mn2O3, δ-MnO2, β-MnO2 ), unless otherwise stated, the batteries are assembled in the same manner.
[0142] For the electrodeposition test, a carbon nanotube (CNT) sheet was used as the cathode. To prepare the cathode substrate, a single-walled carbon nanotube dispersion (SWCNT, 13% (w / v) in water, Jiacai Technology Co., Ltd., Shanghai, China) was diluted 20 times with deionized water and stirred at 70 °C for 2 hours. The solution was then filtered through a hydrophilic PTFE membrane by vacuum filtration to obtain a free-standing CNT electrode with a thickness of about 10 μm. The CNT electrode was then coupled with a Zn anode and made into a button cell, similar to the MnO2-Zn battery.
[0143] 3. Electrochemical testing
[0144] Constant-galvanostatic charge-discharge tests were performed between 0.8 V and 1.8 V using a Neware battery tester (Neware, Shenzhen, China). Cyclic voltammetry (CV, scan rate 0.1 mVs -1 ) and electrochemical impedance spectroscopy (EIS, frequency range from 1 MHz to 0.01 Hz) measurements.
[0145] For the electrodeposition test, the cell was first charged at 0.05 mA cm -2 The cells were charged with a constant current to 1.8 V, followed by a constant voltage step until the areal capacity reached 0.5 mAh cm -2 , then at 0.05 mA cm -2 Discharge to 0.8V.
[0146] 4. Characterization
[0147] The morphological evolution of the electrodes was characterized by scanning electron microscopy (SEM, QUATTROS), energy dispersive X-ray (EDX) spectroscopy and transmission electron microscopy (TEM, JEOL 2100F). X-ray photoelectron spectroscopy (XPS, ThermoScientific Escalab), X-ray diffraction (XRD, Panalytical X'Pert3X-ray diffractometer, Cu Kα radiation source, ) and Raman spectroscopy (WITec RAMAN alpha 300R@R7167 BOC) were used to study the crystal structure changes of the electrodes. Nitrogen adsorption tests were performed at 77K using Micromeritics 3Flex to obtain the Brunauer-Emmett-Teller (BET) surface area. Mn in the electrolyte was detected using inductively coupled plasma atomic emission spectrometry (ICP-AES, PE optima 6000). 2+ Ion concentrations were calculated and each data point was measured three times. To prepare the electrolyte sample for inductively coupled plasma (ICP), all components disassembled from the button cell were soaked in 20 ml of deionized water and stirred overnight before sampling.
[0148] 5. Density functional theory calculations
[0149] Density functional theory (DFT) calculations were performed using the Quantum Espresso software package. GBRV ultrasoft pseudopotentials were used with the PBE exchange-correlation functional. The wave function and enhanced charge density cutoffs were set to 40Ry and 280Ry, respectively. The PBE+U correction was introduced into the Mn atoms with a U value of 4 eV. Both the MnO2 and ZnMn2O4 systems were sampled using Γ-points, where the lattice parameters were obtained from the XRD measurements mentioned above. In the case of MnO2, the lattice parameters obtained from XRD match the ramsdellite phase. Therefore, the lattice parameters used were Mn 32 O 64 For the ZnMn2O4 system, the lattice parameters are Zn 16 Mn 32 O 64 Tetragonal simulation unit cell. Starting from the original MnO2 and ZnMn2O4 systems, Ti-doped MnO2 and ZnMn2O4 systems were generated by replacing randomly selected Mn atoms with Ti atoms in sequence. Finally, for the Zn metal system, the lattice parameters were used. and a 2 × 2 × 2 hexagonal supercell with a k-point sampling of 8 × 8 × 8, with 16 Zn atoms per simulation cell.
[0150] Formation Mechanism of Zn-Mn Oxide
[0151] In this example, commercial EMD was selected as the active material to study the MnO2-Zn battery. The EMD electrode was prepared using the above method. It was matched with 1Zn+0.1Mn electrolyte and the discharge process was started at 1200mA g -1 Galvanostatic tests were performed at current densities ranging from 0.8 V to 1.8 V. Ex situ SEM, XRD, and ICP analyses were performed to investigate the changes in phase and cathode morphology during cycling.
[0152] Figures 5A to 5E The SEM images of the EMD cathode at different voltages in the first cycle are shown in FIG. Figure 5A In the open circuit voltage, the cathode is mainly composed of compact EMD particles. When the battery is discharged to 1.2 V, flake products gradually appear on the electrode surface ( Figure 5B When the battery is fully discharged to 0.8V, the electrode surface is completely covered with flakes ( Figure 5C As the charging process progresses, the flakes gradually disappear and the initial granular morphology is observed again ( Figure 5D and 5E ).
[0153] Figure 5H The first cycle is shown in Fig. 5F) XRD patterns of the cathode in different states. It is found that the peak of zinc sulfate hydroxide (ZHS, Zn4SO4(OH)6·4H2O, JPCDS#44-0673) grows during discharge and disappears during charge, especially the main peak at 8.5°. This is consistent with the observation of the flakes in the SEM results.
[0154] It is known that ZHS precipitation and dissolution are caused by the increase and decrease of electrolyte pH, respectively, which indicates that a proton-mediated reaction (PCR) occurs during the discharge-charge process. The PCR in the MnO2-Zn system is still controversial, but there are two generally recognized pathways:
[0155] 1) H + Embedding and unembedding reactions:
[0156] or
[0157] 2) Mn dissolution / deposition reaction:
[0158] Meanwhile, during the first discharge from state B to state D, the initial XRD peaks of EMD at 37.0° and 42.6° weakened with the appearance of the ZHS phase. During the charging process, the ZHS peak gradually disappeared, while the EMD peak reappeared until the fully charged state G. However, the possibility of these two pathways cannot be ruled out, because the weakening of the EMD peak in the discharged state may be caused by the disordered H + This is caused by the embedding of EMD phase or partial dissolution of EMD.
[0159] A straightforward approach to distinguish these two processes and quantify the contribution of the Mn dissolution / deposition reactions is to measure the Mn 2+ Concentration. During the first cycle, Mn 2+ The ICP results of the concentration are as follows Figure 5G As shown in. Since the electrolyte contains 0.1MMnSO4, the initial Mn 2+ The concentration is 100mM. During the initial discharge process, Mn 2+ The concentration increases linearly around 30 mM, which indicates that the capacity occupied by Mn dissolution is 107.2 mAh g -1 (42.8% of the observed capacity.) The remaining 57.2% of the capacity is likely to come from proton intercalation (Eq. (1)).
[0160] Calculation method:
[0161] The average mass loading of EMD was 1.5 mg cm -2 , and the area of the electrode disk with a diameter of 16 mm is 2 cm-2 Since the molecular weight of MnO2 is 87 g mol -1 , so the total number of moles of Mn in the cathode is:
[0162] 1.5 mg cm -2 ×2cm 2 ÷87 g mol -1 =0.0345mmol
[0163] Mn dissolved in 0.2 ml electrolyte after the first discharge 2+ The increase is:
[0164] 30mM×0.2ml=0.006mmol
[0165] The percentage of Mn dissolved from the EMD active material after the first discharge = 0.006 / 0.0345 = 17.4%.
[0166] Since Mn dissolution is 2e - transport reaction, with a total capacity of 616 mAh g -1 , so the capacity contributed by Mn dissolution is
[0167] 616mΛhg -1 ×17.4%=107.2mΛhg -1
[0168] Since the total capacity of the first discharge is 250 mAh g -1 , so about 107.2 mAh g -1 / 250mAh g -1 = 42.8% of the initial discharge capacity is contributed by Mn dissolution.
[0169] When the MnO2 electrode is charged, Mn 2+ The content decreased, indicating that it was redeposited on the electrode. After the first charge (state G, the charge capacity was 244 mAh g -1 ), Mn 2+ The concentration dropped back to close to the initial value of 100 mM.
[0170] The contribution of Mn redeposition to the initial charge capacity was further analyzed by the following electrolyte-swapping experiment. The EMD electrodes were initially discharged to 0.8 V in 1Zn+0.1Mn electrolyte. The cells were then disassembled and the EMD electrodes were carefully washed with deionized water to remove the electrolyte. The electrodes were then reassembled into cells using ZnSO4 electrolyte without MnSO4 and charged. Figure 6 The charging curve of the battery after the electrolyte is replaced is shown in FIG. Fig. 5FSpecifically, the conventional MnO2-Zn battery without electrolyte replacement shows a first coulombic efficiency of about 100% ( Fig. 5F ), but no dissolved Mn 2+ The electrolyte-replaced cell showed only 145 mAh g due to the lack of MnO2 redeposition. -1 The charge capacity is 59.2% of the discharge capacity. The obtained capacity is consistent with the capacity obtained by proton deintercalation as calculated above, which also confirms that the dissolved Mn 2+ The redeposition of is an important process contributing to the charge capacity.
[0171] It is noteworthy that even if 0.1 M MnSO4 is pre-doped in the electrolyte, a considerable amount of Mn still dissolves, which produces the reversible capacity. This observation is consistent with the commonly believed 2+ The additive can inhibit the dissolution of Mn caused by the Jahn-Teller effect. In fact, the MnO2-Zn system is regarded as a partial electrolytic Mn-Zn battery. 2+ Additives can act as a Mn reservoir to promote Mn 2+ The redeposition of MnO2 can improve the reversibility of the MnO2 dissolution / deposition reaction. The effect is more obvious when the electrolyte is in excess. Figures 7A to 7C The first cycle charge-discharge curves of MnO2-Zn cells in 1MZnSO4 electrolyte with or without MnSO4 additive are shown in lean electrolyte button cells (200μL) and rich electrolyte beaker cells (5ml). For both cells with 1Zn+0.1Mn electrolyte, they show similar voltage curves, capacities, and first cycle efficiencies because of the presence of sufficient Mn in the electrolyte. 2+ , which can be redeposited during the charging process. On the other hand, the cells tested in 1 M ZnSO4 exhibited much lower rechargeable capacity in the beaker cell with excess electrolyte compared to the coin cell configuration. This is because the dissolved Mn 2+ The ions diffuse from the electrode surface into the bulk of the electrolyte and are more difficult to redeposit if the electrolyte volume is larger.
[0172] Although Mn in the electrolyte 2+ The addition of ZnO2 improves the cyclability of MnO2 electrodes by promoting Mn dissolution / deposition, but capacity decay is still observed during long-term cycling due to the formation of inactive Zn-Mn-O phase. Fig.5IAs shown, after 5 cycles, the weak ZnMn2O4 XRD peaks at 32.9° and 36.4° (JPCDS#24-1133) replaced the original EMD peak. After 300 cycles, the characteristic XRD peak of ZnMn3O7 (JPCDS#47-1825) appeared at 18.5°. We can find that these Zn-containing phases exist in both the discharge and charge states after 300 cycles, and their X-ray peak intensities increase with the increase in the number of cycles, which indicates their irreversibility and accumulation. At the same time, the peak intensity of ZHS weakens with the cycle, which is consistent with the reduced reversible capacity generated by self-PCR, which will be further discussed in the following section. These Zn-containing phases can be converted into ZnHs during the charge process according to the following equation due to Zn 2+ and Mn 2+ The co-deposition of:
[0173] xZ 2+ +yMn 2+ +H2O→Zn x Mn y O+2H + +(2-2x-2y)e - (4)
[0174] Since these phases are known to be electrochemically inactive with low conductivity, their formation is believed to consume active Mn and hinder ion transport in the electrode. This degradation process will be accelerated in MnO2 electrodes that exhibit larger capacities, where Mn dissolution / deposition contributes more to the capacity, while it may not be significant when the capacity is lower at high current rates. This may explain why some previous studies on MnO2-Zn batteries were able to exhibit high stability at relatively low capacity utilization because fewer inactive phases were formed in each cycle. In order to maintain MnO2 electrodes with high capacity for practical applications, the present application unexpectedly provides a method for suppressing the formation of inactive Zn-Mn-O phases with cycling.
[0175] In-situ doping
[0176] In order to solve the above technical problems existing in the prior art, the inventors introduced metal / metalloid ion salts, such as TiOSO4, into the electrolyte as a doping source to pass through Mn during the charging process. 2+ and TiO 2+ It has been found that the cycling stability of the EMD electrode is significantly improved after the addition of TiOSO4 to the electrolyte (as discussed in the following section), and the formation of the Zn-containing phase is suppressed during cycling.
[0177] To clarify the role of TiOSO4 additives, we designed Fig. 8AThe electrodeposition test shown in the figure only undergoes the Mn deposition / dissolution process. A bare CNT film is used as the cathode, and 1Zn+0.4Mn with and without 0.5% TiOSO4 additive is used as the electrolyte. It should be noted that the MnSO4 content in the electrolyte in the electrodeposition test is higher than that in the battery test to promote Mn deposition. By charging at a constant voltage of 1.8V, the Mn in the electrolyte 2+ The battery was charged to a capacity of 0.5 mAh cm -2 (Assuming 2e - transmission, corresponding to 0.81 mg cm -2 MnO2 deposition) and then discharge. Figure 8B From the voltage curves shown in , it can be seen that the battery tested in 1Zn+0.4Mn+0.5Ti electrolyte exhibits a larger initial discharge capacity than the battery tested in 1Zn+0.4Mn electrolyte. Similar behavior is observed at different areal capacity limits ( Figures 9A to 9C ). This indicates that the EMD deposited with TiOSO4 additive has higher reversibility. In addition to the higher 1st cycle reversibility, the EMD deposited in 1Zn+0.4Mn+0.5Ti electrolyte also shows improved cyclability ( Fig. 10A and 10B ).
[0178] SEM and EDX were used to investigate the morphology and composition of the deposited EMD after charging. The original CNT electrode showed a smooth surface ( Figure 8C ), while the EMD deposited in 1Zn+0.4Mn electrolyte exhibits a flake-like structure ( Fig.8D ), while when containing TiOSO4, it appears granular ( Fig. 8E ).EDX Image( Fig.8F ) shows that the different elements are evenly distributed in the deposited samples, with a small amount of Zn present in the EMD deposited without TiOSO4, and Ti present in the EMD deposited with TiOSO4. The specific atomic ratios are listed in Table S1.
[0179] Table S1. Atomic percentage of each element in the deposited EMD after charging in different electrolytes.
[0180]
[0181] For both samples, because the deposited product is mainly MnO2, Mn and O are the main elements. At the same time, no S element was observed in either sample, and it is speculated that S was not incorporated into the material, and the electrolyte was completely removed during the cleaning process. Therefore, the Zn element observed in the EMD deposited without TiOSO4 is not due to residual electrolyte, but due to the co-deposition of Zn and Mn during the charging process. In contrast, the material deposited in the 1Zn+0.4Mn+0.5Ti electrolyte shows very little Zn content, while the Ti content is about 3%. This indicates that Ti rather than Zn is preferably doped into the EMD.
[0182] To more fully analyze the above electrodes, additional characterizations were applied. Fig.11A The XRD patterns in confirm that the two deposited products are mainly EMD, whose peaks are similar to those of commercial EMD. For the sample deposited in 1Zn+0.4Mn, small peaks corresponding to ZnMn2O4 and ZnMn3O7 can be observed, indicating that in addition to the main reaction, there are also Zn-containing byproducts from EMD deposition. The formation of these inactive phases can explain why the capacity of MnO2-Zn batteries gradually decreases with cycling. On the other hand, the peaks of EMD deposited in 1Zn+0.4Mn+0.5Ti electrolyte are broader, which is attributed to the reduced crystallinity of EMD when Ti doped.
[0183] Fig. 11B The Raman spectra of the two electrodes were compared in Figure 2. The EMD deposited in the TiOSO4-containing electrolyte only showed a similar peak at 636 cm-1 as the commercial EMD. -1 The Mn-O peak at 486 cm-1 is shown in Figure 2, while the electrode deposited in 1Zn+0.4Mn electrolyte contains a peak at 486 cm-1. -1 An additional peak at , which can be attributed to Zn x Mn y Zn-O peak in O phase.
[0184] We also analyzed the samples using XPS to further investigate the valence state of Mn. Fig. 11C As shown in , the Mn 2p spectrum can be deconvoluted into Mn 4+ and Mn 3+ Compared with the electrodes deposited in commercial EMD and containing TiOSO4, the Mn 2p peak of the electrode deposited in 1Zn+0.4Mn shifts to a lower binding energy, indicating that the Mn 3+The contribution of the peak is higher. In addition, the splitting amplitude of the Mn 3s peak of the electrode in 1Zn+0.4Mn is also increased compared with the other two samples (Figure 11d). Due to the coupling of non-ionized 3s electrons with 3d valence band electrons, the amplitude of the splitting of the Mn 3s peak depends on the oxidation state of Mn. Therefore, both the Mn 2p and 3s spectra reveal that the average oxidation state of Mn in the deposited EMD without Ti is lower. This is consistent with the presence of the ZnMn2O4 product with a Mn valence of 3+ as shown in the XRD analysis. The Zn 2p XPS peak can be observed from the electrode, verifying the co-deposition of Zn and Mn ( Fig.11F and Figures 12A to 12C ).
[0185] On the other hand, the EMD deposited in the TiOSO4-containing electrolyte mainly shows 4+ This indicates that Ti not only inhibits the formation of Zn-containing products but also has little effect on the valence state of Mn in the products. A small amount of Ti is incorporated into the deposited EMD, as the Ti 2p XPS peak can be observed in the electrode made of TiOSO4 ( Fig.11E and Figures 12A to 12C ), which is consistent with the EDX results (Table S1).
[0186] Although we found Ti in the deposited EMD electrode, there are three possible forms of Ti: TiO2, Ti in the EMD tunnel, or dopant in the EMD framework. First, from the Raman spectrum and XRD patterns of the electrode ( Fig.13A and 13B ) no TiO2 can be detected. Secondly, because the total length of the Ti-O bond is about Size and The tunnel of the EMD is probably not large enough to accommodate the Ti element. Fig.14 As shown in the example, since Mn and Ti have similar size, charge and coordination number, it is more likely that Ti 4+ It is incorporated into the MnO6 octahedral unit of EMD.
[0187] To understand why Ti-doped EMD can suppress the formation of Zn-containing phases, first-principles DFT calculations were further performed. First, we calculated the formation energy (ΔE) of EMD(MnO2) and compared it with the formation energy of ZnMn2O4. We found that the ΔE per Zn atom of ZnMn2O4 is 3.24 eV, which is lower than that of MnO2, indicating that Zn is more energetically favorable to be incorporated into the structure ( Fig.11G Then, we gradually replaced the Mn atoms in the framework with Ti (Ti x Mn 32-x O 64 )( Fig.11H ) and calculated the energy required to incorporate Zn into it. Our results show that the formation energy of Zn-containing compounds increases with Ti substitution, indicating that Ti doping in the EMD structure inhibits the incorporation of Zn into the structure, which is consistent with the experimental results.
[0188] Example 1
[0189] Electrochemical performance
[0190] To explore the benefits of adding TiOSO4, Figures 15A-15J The electrochemical performance of EMD-Zn batteries using different electrolytes is shown in Figure 1. The CV curve of the battery using 1Zn+0.1Mn+0.5Ti electrolyte shows two unique redox peaks, which can also be observed in the batteries using 1M ZnSO4 and 1Zn+0.1Mn electrolytes. Because the capacity of the bare KB cathode without EMD is negligibly low ( Fig.16 ), the redox peaks were confirmed to originate from the charge-discharge reaction of EMD. The CV results showed that the TiOSO4 additive had little effect on the main redox reaction of EMD.
[0191] Fig. 15B The rate performance of EMD tested in different electrolytes is shown in Figure 2. It can be seen that adding MnSO4 additive to the electrolyte can improve the rate performance of EMD. This is attributed to the higher content of Mn in the electrolyte. 2+ Improved Mn during charging 2+ The redeposition kinetics of the EMD electrodes were investigated using the 1Zn+0.1Mn+0.5Ti electrolyte at 1C, 2C, 4C, 8C, 12C, 16C, and 20C (1C = 300 mA g -1 ) shows 302mAh g at the current rate -1 , 275mAh g -1 , 250mAh g -1 、212mAhg -1 , 165mAh g-1, 136mAh g-1 -1 、118mAh g-1 The corresponding voltage curve is as follows: Fig.17 as shown in .
[0192] Battery at 1200mAg -1 The cycling performance under current is as follows Fig. 15CThe EMD tested in 1MZnSO4 electrolyte showed rapid capacity decay, while the battery using 1Zn+0.1Mn showed better cycling stability and slower capacity decay, which is consistent with the observations of many other literatures. However, the capacity still dropped suddenly after about 200 cycles. In contrast, the battery tested with 1Zn+0.1Mn+0.5Ti electrolyte showed a significant improvement in cyclability. After 1500 cycles, it still showed 230mAh g -1 The capacity of , compared with the initial cycle capacity, corresponds to a capacity retention of approximately 100%. Figures 15D to 15F The voltage curves of the three batteries at different cycle numbers are shown in Figure 1. Unlike the batteries in 1M ZnSO4 and 1Zn+0.1Mn, which show a sharp capacity decay, the battery tested in 1Zn+0.1Mn+0.5Ti shows overlapping discharge-charge curves after 1500 cycles. In addition, the cycling stability of the EMD electrode at different current densities using the TiOSO4 electrolyte additive is also improved. Figure 15G As shown in Figure 4H, the battery using 1Zn+0.1Mn+0.5Ti electrolyte has a high current density of 3600mAg -1 After 6000 cycles, 113 mAh g -1 capacity, and at 4800mAg -1 After 10,000 cycles, 92 mAh g -1 The capacity is better than that of the battery using 1Zn+0.1Mn (at 3600mAg -1 After 3500 cycles, it is 73 mAh g -1 , and at 4800mAg -1 60mAh g after 3000 cycles -1 ).like Fig.15I As summarized in Table S2, the cycling performance is also the best among the recently reported MnO2-Zn batteries. Fig.15J ) shows that the MnO2-Zn battery using 1Zn+0.1Mn+0.5Ti electrolyte has a power density of 390W kg -1 (calculated based on the mass of the cathode active material), the energy density provided is 390Wh kg -1 , and when the power density increases to 7800W kg -1 , still maintain 153Whkg -1 The energy density of ZIBs is better than that of most previously reported ZIBs.
[0193] Table S2. Comparison of cycling performance with recent literature.
[0194]
[0195] Example 2
[0196] In the following examples, different electrolytes were used, including a basic electrolyte (1MZnSO4+0.1M MnSO4), with or without additives according to the present application. EMD was used as the electrode material. A rechargeable manganese zinc battery was prepared using the same method as described above.
[0197] Cycling performance is defined as the ratio of the capacity of the manganese zinc battery at the 200th cycle to the capacity at the 2nd cycle at a current rate of 900 mA / g. The battery was cycled at 900 mA / g between 0.8 and 1.8 V. The capacity (in mAh) was obtained from the battery tester divided by the mass of EMD in the cathode (in mg).
[0198] CE-1: Basic electrolyte (1MZnSO4+0.1MMnSO4), without additives
[0199] like Fig.18 As shown in , the capacity of the battery during the 2nd cycle was 277 mAh / g. However, its capacity decreased to 133 mAh / g at the 200th cycle, with a cycling performance of 48%.
[0200] E2-1: Basic electrolyte (1MZnSO4+0.1MMnSO4), containing TiOSO4 as electrolyte additive (Ti 4+ / TiO 2 + )
[0201] The electrodes and cells were prepared in the same manner as CE-1, except that different amounts of TiOSO4 were added to the 1M ZnSO4+0.1MMnSO4 base electrolyte. For example, the "+0.5% (w / v) TiOSO4" electrolyte means that 0.5g TiOSO4 was added to 100ml of the base electrolyte and stirred overnight at room temperature. Therefore, unless otherwise stated, the percentage content of additives in this article refers to weight / volume (w / v) percentage. Electrolytes containing other amounts of additives were prepared in the same way.
[0202] Fig.18 The capacity versus cycle curves are shown in Figure 1 and the cycling performance is summarized in Table 1. The inclusion of TiOSO4 additive in the electrolyte improves the cycling performance as it increases from 48% without additive (CE-1) to 77.0% with +0.2% (w / v) TiOSO4 (E2-1a), to 116.8% with +0.5% (w / v) TiOSO4 (E2-1b), and to 93.2% with +2% (w / v) TiOSO4 (E2-1d). Specifically, the cell with 0.5% (w / v) TiOSO4 maintains 292 mAh g after 200 cycles. -1 High capacity.
[0203] In addition, the cycling performance was improved to 115.0% when +5% (w / v) TiOSO4 (E2-1f) was used. However, it was further noted that the capacity obtained was reduced from the baseline level of 277 mAh / g to 100 mAh / g, which is less than the capacity of the baseline electrolyte without electrolyte additives after 200 cycles. Therefore, in order to improve the cycling performance without sacrificing the overall capacity of the battery, the percentage of the electrolyte additive is expected to be in the range of about 0.1% (w / v) to about 5% (w / v).
[0204] Table 1. Comparison of cycling performance of electrolytes with different contents of TiOSO4 electrolyte additives
[0205]
[0206]
[0207] In fact, the stability of EMD may be affected by the amount of TiOSO4 additive. Fig.18 The cycling performance of EMD in 1Zn+0.1Mn containing different amounts of TiOSO4 is shown. It can be seen that adding 0.2% (w / v) TiOSO4 can reduce the capacity decay to some extent. On the other hand, too much TiOSO4 reduces the total capacity. These examples show that 0.5% (w / v) may be the optimal amount to achieve a good balance between stability and capacity.
[0208] Example 3
[0209] The preparation method of the rechargeable manganese-zinc battery is the same as that of Example 2.
[0210] The effect of Ti additives on the EMD structure was further investigated by post hoc testing, such as Fig.5I and Figures 19A to 19K as shown in .
[0211] In order to understand the reason for the improvement of cycle performance, XRD analysis was performed on the MnO2 electrode in Example 2 after a certain cycle ( Fig.5I and 19A ).
[0212] For electrodes using basic electrolyte circulation ( Fig.5I ), due to the discharge process H + The consumption of H +Due to the insertion and dissolution of MnO2, after the 5th discharge, the initial EMD peak turned into a zinc hydroxide sulfate (ZHS) peak, while after charging, the ZnMn2O4 peak was found. After 300 cycles, the ZHS peak in the discharge state became weaker, and the ZnMn3O7 peak began to appear. The presence of ZnMn2O4 and ZnMn3O7 peaks in both the discharge and charge states indicates the irreversibility of these phases. After 500 cycles, the ZnMn3O7 peak became stronger. Overall, in the baseline electrolyte without additives, inactive Zn x Mn y O phase, resulting in a decrease in capacity with cycling.
[0213] In contrast, when 0.5% (w / v) TiOSO4 was added ( Fig.19A ), the MnO2 XRD peak can still be observed in the charged state even after 500 cycles, indicating that the additive can reduce the Zn x Mn y O phase and stabilize the MnO2 structure, thereby improving the cycle performance.
[0214] Fig.19A The XRD patterns of the battery using 1Zn+0.1Mn+0.5Ti after different cycles are shown in Figure 2. Fig.5I The XRD patterns of the battery using 1Zn+0.1Mn are different. The EMD peak and ZHS peak observed in the charge and discharge states are well maintained over 500 cycles, respectively, and almost no Zn-containing phase is observed. In addition, the morphological changes of the electrodes after cycling were examined by SEM and TEM, such as Fig.19B After 500 cycles, the electrode tested in 1Zn+0.1Mn showed nanosheets on its surface similar to those reported in the literature. The HRTEM image of the electrode showed lattice fringes attributed to (002) of ZnMn3O7 and (211) of ZnMn2O4, which is consistent with the Fig.5I On the other hand, the electrode cycled in 1Zn+0.1Mn+0.5Ti electrolyte exhibits nanoparticle morphology, which is consistent with the XRD peaks at 18.5° and 36.4° in the electrolyte. Fig.8D and 8E The morphology of the electrodeposited materials observed in Figure 2 is consistent with that of the samples, and the HRTEM images only show the long-range (131) lattice fringes of EMD. All the above results clearly indicate that the addition of TiOSO4 suppresses the formation of Zn-containing phases and improves the reversibility of EMD.
[0215] Example 4
[0216] The preparation method of the rechargeable manganese-zinc battery is the same as that of Example 2.
[0217] In this example, ICP analysis was used to systematically monitor the Mn content in the electrolyte. 2+ The changes of Mn concentration over the cycles were investigated to better reveal the relationship between the Mn dissolution / deposition process and the electrochemical performance of EMD. Overall, we observed that during the discharge process, Mn 2+ During the charging process, due to the deposition of Mn, its concentration decreases. 2+ The total amount will change with the cycle. Fig.19D As shown in Figure 2, in the battery tested using 1M ZnSO4 electrolyte without any additives, the Mn 2+ The content increases within the first 100 cycles, indicating that Mn dissolution is greater than Mn deposition. This may be because there is no Mn in the electrolyte at the beginning. 2+ , so the dissolved Mn 2+ After 100 cycles, the Mn 2+ The concentration begins to decrease due to the irreversible formation of Zn-containing Mn oxide species that consumes Mn 2+ .
[0218] Adding 0.1M MnSO4 to the electrolyte changes the Mn 2+ With the overall trend of the cycle ( Fig.19E ). During discharge and charge, Mn 2+ The concentrations increased and decreased, respectively, and during the initial cycle, the concentration value remained around 0.1 M, which indicated that Mn 2+ Additives can effectively promote Mn 2+ However, with further cycling, the 2+ As the content of Mn continues to decrease, 2+ Irreversible consumption occurs, and the formation of Zn-Mn-O still occurs inevitably. It is worth noting that after 300 cycles, Mn 2+ The sharp drop in content and Fig. 15C In contrast, when using the TiOSO4 additive, the Mn 2+ The normal rise and fall of concentration remains stable. The dissolution and deposition of Mn are reversible, and there is no side reaction that consumes Mn with the cycle. This is attributed to the effective inhibition of the deposition of Zn-Mn oxides by the addition of TiOSO4.
[0219] In addition to the consumption of active Mn in the electrolyte, the formation of inactive Zn-Mn oxides can also degrade the electrode. We measured the EIS of each cell at different cycles after charging and Figures 19G to 19IThe Nyquist plot is shown in Figure 1. The EIS curve shows two semicircles, which correspond to the interface resistance R from high frequency to low frequency. i and the charge transfer resistance R ct For these three batteries, R ct The semicircle of increases with the number of cycles. Fig.19J The equivalent circuit fitting curve shown in the figure gives R ct The value of , and the result is Figure 19K Both batteries tested with 1M ZnSO4 and 1Zn+0.1Mn electrolytes showed R ct In contrast, the R ct After 500 cycles, it only slightly increased to 57Ω. This indicates that the addition of TiOSO4 can suppress the impedance growth of the electrode. Based on our previous discussion, R ct The increase in can be attributed to the formation of inactive Zn-Mn oxides on the electrode, which hinders ion diffusion, while TiOSO4 can prevent this reaction.
[0220] Example 5
[0221] In this embodiment, an additive different from TiOSO4 is introduced into the electrolyte to test its effect on battery performance. The preparation method of the rechargeable manganese-zinc battery is the same as that of embodiment 2.
[0222] E5-1: Basic electrolyte (1M ZnSO4+0.1M MnSO4), containing NiSO4 as electrolyte additive (Ni 2+ )
[0223] NiSO4 can also be used as an effective electrolyte additive in this application. The electrodes and cells were prepared in the same manner as CE-1, except that 0.5% (w / v) NiSO4 was added to the 1M ZnSO4+0.1M MnSO4 base electrolyte.
[0224] Fig. 20 The capacity and cycle curves of the manganese-zinc battery using +0.5% (w / v) NiSO4 are shown in Figure 2, and the cycle performance is summarized in Table 2. -1 The battery with +0.5% (w / v) NiSO4 electrolyte has a capacity of 231 mAh g after 200 cycles. -1 , with a cycle performance of 92.0%.
[0225] E5-2: Basic electrolyte (1M ZnSO4+0.1MMnSO4), containing La(NO3)3 as electrolyte additive (La 3+ )
[0226] The electrodes and cells were prepared in the same manner as CE-1, except that 0.5% (w / v) La(NO3)3 was added to the 1M ZnSO4+0.1M MnSO4 base electrolyte.
[0227] Fig.21 The capacity and cycle curves of the manganese-zinc cells using +0.5% (w / v) La(NO3)3 are shown in Figure 2, and the cycle performance is summarized in Table 2. -1 Under the condition of +0.5% (w / v) La(NO3)3 electrolyte, the battery provided a capacity of 172 mAh g after 200 cycles. -1 , with a cycling performance of 61.6%.
[0228] E5-3: Basic electrolyte (1M ZnSO4+0.1M MnSO4) containing FeSO4 and Fe2(SO4)3 as electrolyte additives Agent (Fe 2+ and Fe 3+ )
[0229] The electrodes and cells were prepared in the same manner as CE-1, except that 0.5% (w / v) FeSO4 / 0.5% (w / v) Fe2(SO4)3 was added to the 1M ZnSO4+0.1M MnSO4 base electrolyte.
[0230] Fig. 22 The capacity and cycle curves of the manganese-zinc cells using +0.5% (w / v) FeSO4 (E5-3a) and +0.5% (w / v) Fe2(SO4)3 (E5-3b) are shown in Figure 2, and the cycle performance is summarized in Table 2. -1 Under the same conditions, the cells using +0.5% (w / v) FeSO4 and +0.5% (w / v) Fe2(SO4)3 electrolytes produced 161 and 150 mAh g after 200 cycles, respectively. -1 of capacity and have a cycling performance of 94.7% and 86.2%, respectively.
[0231] E5-4: Basic electrolyte (1M ZnSO4+0.1M MnSO4) containing H3BO3 as electrolyte additive
[0232] The electrodes and cells were prepared in the same manner as CE-1, except that 0.5% (w / v) H3BO3 was added to the 1M ZnSO4+0.1M MnSO4 base electrolyte.
[0233] Fig.23 The capacity and cycle curves of the manganese zinc cells using +0.5% (w / v) H3BO3 (E5-4) are shown in Figure 2, and the cycle performance is summarized in Table 2. -1 The battery with +0.5% (w / v) H3BO3 electrolyte provided a capacity of 177 mAh g after 200 cycles. -1 , with a cycling performance of 69.1%.
[0234] E5-5: Basic electrolyte (1M ZnSO4+0.1M MnSO4), containing MgSO4 as electrolyte additive
[0235] The electrodes and cells were prepared in the same manner as CE-1, except that 0.5% (w / v) MgSO4 was added to the 1 M ZnSO4 + 0.1 M MnSO4 base electrolyte.
[0236] Fig.24 The capacity and cycle curves of the manganese-zinc cells using +0.5% MgSO4 (E5-5) are shown in FIG, and the cycle performance is summarized in Table 2. -1 The battery with +0.5% (w / v) MgSO4 electrolyte provided a capacity of 131 mAh g after 200 cycles. -1 , with a cycling performance of 50.2%.
[0237] Table 2. Comparison of cycling performance of electrolytes containing different types of electrolyte additives
[0238]
[0239]
[0240] Example 6
[0241] In the following examples, different electrode materials were used. The electrolyte and rechargeable manganese zinc battery were prepared using the same method as described above.
[0242] Comparative Example 2 (CE-2): Mn2O3 as electrode material without electrolyte additives
[0243] Electrodes using Mn2O3, Ketjen black and PVdF binder in a weight ratio of 7:2:1 were coated on graphite paper as cathode and Zn foil (50 μm) as anode to form a rechargeable manganese-zinc battery. Mn2O3 was made by annealing EMD powder (Xiangtan Electrochemical Scientific ltd, China) at 550°C for 5 hours. 1M ZnSO4+0.1MMnSO4 was used as the electrolyte, and the battery was cycled between 0.8 and 1.8V at 900mA / g.
[0244] like Fig.25 As shown in , the capacity of the battery during the 2nd cycle was 197 mAh / g. However, its capacity decreased to 83 mAh / g at the 200th cycle, with a cycling performance of 42.1%.
[0245] E6-1: Mn2O3 as electrode material with electrolyte additives
[0246] The electrodes and cells were prepared in the same manner as CE-2, except that 0.5% (w / v) TiOSO4 was added to the 1 M ZnSO4 + 0.1 M MnSO4 base electrolyte.
[0247] Fig.25 The capacity and cycle curves of the manganese-zinc cells using +0.5% (w / v) TiOSO4 are shown in Figure 3, and the cycling performance is summarized in Table 3. -1 The battery with +0.5% TiOSO4 electrolyte provided a capacity of 212 mAh g after 200 cycles. -1 , with a cycle performance of 124.7%.
[0248] Table 3 Comparison of cycling performance of cells containing Mn2O3 in the cathode and with or without electrolyte additives in the electrolyte
[0249]
[0250] Comparative Example 3 (CE-3): δ-MnO2 as Electrode Material without Electrolyte Additive
[0251] The synthesis method of δ-MnO2 is as follows: 3.4 g of MnSO4.H2O powder is dissolved in 20 mL of distilled water at room temperature, and then 30 mL of NaOH (6M) aqueous solution is added dropwise to the solution under vigorous stirring to obtain a light brown slurry of Mn(OH)2. After stirring for about 1 hour, 3.2 g of (NH4)2S2O8 granular mixture is slowly added to the slurry, and olive green Na birnessite (δ-MnO2) powder is extracted from the slurry.
[0252] Electrodes using δ-MnO2, Ketjen black and PVdF binder in a weight ratio of 7:2:1 were coated on graphite paper as cathode and Zn foil (50 μm) as anode to form a rechargeable manganese-zinc battery. 1M ZnSO4+0.1M MnSO4 was used as the electrolyte and the battery was cycled between 0.8 and 1.8 V at 900 mA / g.
[0253] like Fig.26 As shown in , the capacity of the battery during the 2nd cycle was 296 mAh / g. However, its capacity decreased to 177 mAh / g at the 200th cycle, with a cycling performance of 59.8%.
[0254] E6-2: δ-MnO2 as electrode material with electrolyte additives
[0255] The preparation method of electrodes and cells was the same as that of CE-3, except that 0.5% (w / v) TiOSO4 was added to the 1M ZnSO4+0.1M MnSO4 base electrolyte.
[0256] Fig.26 The capacity and cycle curves of the manganese-zinc cells using +0.5% (w / v) TiOSO4 are shown in Figure 4, and the cycling performance is summarized in Table 4. -1Under the condition of +0.5% (w / v) TiOSO4 electrolyte, the battery provided a capacity of 300 mAh g after 200 cycles. -1 , with a cycle performance of 99.0%.
[0257] Table 4 Comparison of cycling performance of cells containing δ-MnO2 in the cathode and with or without electrolyte additives in the electrolyte
[0258]
[0259] Comparative Example 4 (CE-4): β-MnO2 as an electrode material without electrolyte additives
[0260] Electrodes using β-MnO2 (Alfa Aesar, USA), Ketjen black and PVdF binder in a weight ratio of 7:2:1 were coated on graphite paper as cathode and Zn foil (50 μm) as anode to form a rechargeable manganese zinc battery. 1M ZnSO4+0.1M MnSO4 was used as the electrolyte, and the battery was cycled between 0.8 and 1.8 V at 900 mA / g.
[0261] like Fig. 27 As shown in , the capacity of the battery during the 2nd cycle was 246 mAh / g. However, its capacity decreased to 138 mAh / g at the 200th cycle, with a cycling performance of 56.1%.
[0262] E6-3: β-MnO2 as electrode material and its content 0.5%(w / v)TiOSO4 Base electrolyte
[0263] The electrodes and the battery were prepared in the same manner as in Comparative Example 4, except that 0.5% (w / v) TiOSO4 was added to the 1M ZnSO4 + 0.1M MnSO4 base electrolyte.
[0264] Fig. 27 The capacity and cycle curves of the manganese-zinc cells using +0.5% (w / v) TiOSO4 are shown in Figure 4, and the cycling performance is summarized in Table 4. -1 The battery with +0.5% TiOSO4 electrolyte provided a capacity of 258 mAh g after 200 cycles. -1 , with a cycle performance of 104.8%.
[0265] Table 5 Comparison of cycling performance of batteries containing β-MnO2 in the cathode and containing or not containing electrolyte additives in the electrolyte
[0266]
[0267] It is believed that the present application can greatly improve the cycle performance of aqueous rechargeable manganese-zinc battery systems, which can promote their application. Manganese-zinc batteries use aqueous electrolytes, which have the characteristics of low cost, intrinsic safety and moderate energy density. It is a new type of rechargeable battery that can replace the lead-acid batteries widely used in automotive applications. In addition, rechargeable manganese-zinc batteries can be used for grid-scale energy storage, such as power plants, renewable energy storage, etc., and can also replace disposable primary alkaline batteries.
[0268] Lead-acid batteries are the main technology / product for aqueous-based batteries in the market. Lead-acid batteries are commonly used in automotive applications, but the toxicity of lead can cause serious environmental issues. In rechargeable manganese-zinc batteries, both electrodes are safe and non-toxic. In particular, the electrode materials are cheap (the price of metallic Zn is below $3,000 / ton (London Metal Exchange), while the price of MnO2 is around $1,000 / ton (from Alibaba survey)), resulting in an estimated cost of about $23 / kWh for a full manganese-zinc battery, which is much lower than lead-acid batteries (about $70 / kWh) and lithium-ion batteries (about $200 / kWh). In addition, the mature process for manufacturing alkaline MnO2-Zn batteries can be directly transferred to the preparation of rechargeable manganese-zinc batteries. In addition, our rechargeable manganese-zinc battery exhibits excellent stability and its performance may exceed that of lead-acid batteries. In addition, considering only the electrodes and electrolyte, the theoretical energy density of lead-acid batteries is 167Wh / kg (the actual energy density is 30-40Wh / kg), while the theoretical energy density of rechargeable manganese-zinc batteries is 209Wh / kg. Taking into account other components in the battery, the actual energy density of rechargeable manganese-zinc batteries will be about 40-50Wh / kg, which is higher than that of lead-acid batteries.
[0269] Overall, the rechargeable manganese-zinc batteries manufactured using our application will have lower cost and higher energy density than the lead-acid batteries used in the market.
[0270] It should be understood that the foregoing merely illustrates and describes embodiments according to which the present application may be implemented, and that modifications and / or changes may be made thereto without departing from the spirit of the present application.
[0271] It should also be understood that certain features of the present application described in the context of separate embodiments for clarity may also be provided in combination in a single embodiment. Conversely, various features of the present application described in the context of a single embodiment for brevity may also be provided separately or in any suitable sub-combination.
[0272] References
[0273] [1]J.Zhang,W.Li,J.Wang,X.Pu,G.Zhang,S.Wang,N.Wang,X.Li,Engineering p-Band Center of Oxygen Boosting H + Intercalation in δ-MnO2 for Aqueous Zinc IonBatteries,Angewandte Chemie International Edition.62(2023)e202215654.
[0274] [2]Y.Wu,J.Zhi,M.Han,Z.Liu,Q.Shi,Y.Liu,P.Chen,Regulating protondistribution by ion exchange resin to achieve long lifespan aqueous Zn-MnO2battery,Energy Storage Materials.51(2022)599-609.
[0275] [3]Y.Zhao,R.Zhou,Z.Song,X.Zhang,T.Zhang,A.Zhou,F.Wu,R.Chen,L.Li,Interfacial Designing of MnO2 Half-Wrapped by Aromatic Polymers for High-Performance Aqueous Zinc-Ion Batteries,Angewandte Chemie InternationalEdition.61(2022)e202212231.
[0276] [4]H.Yang,W.Zhou,D.Chen,J.Liu,Z.Yuan,M.Lu,L.Shen,V.Shulga,W.Han,D.Chao,The origin of capacity fluctuation and rescue of dead Mn-based Zn-ionbatteries:a Mn-based competitive capacity evolution protocol,Energy&Environmental Science.15(2022)1106-1118.
[0277] [5]L.Liu,Y.-C.Wu,L.Huang,K.Liu,B.Duployer,P.Rozier,P.-L.Taberna,P.Simon,Alkali ions pre-intercalated layered MnO2 nanosheet for zinc-ionsstorage,Advanced Energy Materials.11(2021)2101287.
[0278] [6]S.Wang,Z.Yuan,X.Zhang,S.Bi,Z.Zhou,J.Tian,Q.Zhang,Z.Niu,Non-metalion co-insertion chemistry in aqueous Zn / MnO2 batteries,Angewandte Chemie.133(2021)7132-7136.
[0279] [7]J.Ji,H.Wan,B.Zhang,C.Wang,Y.Gan,Q.Tan,N.Wang,J.Yao,Z.Zheng,P.Liang,J.Zhang,H.Wang,L.Tao,Y.Wang,D.Chao,H.Wang,Co 2+ / 3+ / 4+ -regulated electronstate of Mn-O for superb aqueous zinc-manganese oxide batteries,AdvancedEnergy Materials.11(2021)2003203.
[0280] [8]X.Yang,Z.Jia,W.Wu,H.-Y.Shi,Z.Lin,C.Li,X.-X.Liu,X.Sun,The back-deposition of dissolved Mn 2+ to MnO2 cathodes for stable cycling in aqueouszinc batteries,Chemical Communications.58(2022)4845-4848.
[0281] [9]T.Sun,Q.Nian,S.Zheng,J.Shi,Z.Tao,Layered Ca 0.28MnO2·0.5H2O as a high performance cathode for aqueous zinc-ion battery, Small.16(2020)2000597.
[0282]
[10] Q.Duan, Y.Wang, S.Dong, DYWYu, Facile electrode additivestabilizes structure of electrolytic MnO2 for mild aqueous rechargeable zinc-ion battery, Journal of Power Sources.528(2022)231194.
[0283] All references specifically cited herein are hereby incorporated by reference in their entirety. However, citation or incorporation of such references does not necessarily constitute an admission of their appropriateness, citableness, and / or availability as prior art for or with respect to the present application.
Claims
1. An electrolyte for a battery comprising a manganese-based cathode, the electrolyte further comprising a compound of formula M n+ A metal / metalloid ion wherein M represents a metal / metalloid and wherein n is from about 2 to about 4.
2. The electrolyte of claim 1, wherein the metal / metalloid ion is selected from Ti 4+ 、TiO 2+ 、Ni 2+ , Fe 2+ , Fe 3+ ,La 3+ 、Zr 4+ 、ZrO 2+ Sn 2+ 、Bi 3+ 、V 4+ 、V 3+ 、V 2+ 、Al 3+ , Sb 3+ Mg 2+ , Ca 2+ , B 3+ and their combinations.
3. The electrolyte of claim 1, wherein the metal / metalloid ions are present in the form of salts selected from the group consisting of TiOSO4, NiSO4, La(NO3)3, FeSO4, Fe2(SO4)3, H3BO3, MgSO4 and combinations thereof.
4. The electrolyte of claim 1, wherein M n+ The amount is in the range of about 0.1% (w / v) to about 5% (w / v).
5. The electrolyte of claim 1, wherein the metal / metalloid ions are used as an in-situ doping source to form a metal / metalloid doped manganese-based cathode during the charge / discharge process of the battery.
6. A battery comprising a manganese-based cathode comprising a n+ An electrolyte of metal / metalloid ions, wherein M represents a metal / metalloid, and wherein n is from about 2 to about 4.
7. The battery of claim 6, wherein the metal / metalloid ion is selected from Ti 4+ 、TiO 2+ 、Ni 2+ , Fe 2+ , Fe 3+ ,La 3+ 、Zr 4+ 、ZrO 2+ Sn 2+ 、Bi 3+ 、V 4+ 、V 3+ 、V 2+ 、Al 3+ , Sb 3+ Mg 2+ , Ca 2+ , B 3+ and their combinations.
8. The battery of claim 6, wherein the metal / metalloid ion is present in the form of a salt selected from the group consisting of TiOSO4, NiSO4, La(NO3)3, FeSO4, Fe2(SO4)3, H3BO3, MgSO4 and combinations thereof.
9. The battery of claim 6, wherein the electrolyte comprises about 0.05% (w / v) to about 10% (w / v); or about 0.1% (w / v) to about 5% (w / v) of metal / metalloid ions.
10. The battery of claim 6, wherein a metal / metalloid doped manganese-based cathode is formed by in-situ doping during the charge / discharge process of the battery.
11. The battery of claim 6, wherein the manganese-based cathode comprises a cathode material selected from the group consisting of MnO2, MnO, Mn3O4, Mn2O3, MnOOH, and combinations thereof.
12. The battery of claim 11, wherein the cathode material is MnO2.
13. The battery of claim 12, wherein the MnO2 comprises different polymorphs selected from the group consisting of α, β, γ, δ, λ, ramsdellite, and electrolytic manganese dioxide structures.
14. The battery of claim 6, wherein the manganese-based cathode comprises a metal / metalloid doping structure in the cathode after charge / discharge cycles, which prevents the manganese-based cathode from transforming into an electrochemically inert phase.
15. The battery of claim 6, wherein the battery comprises an anode comprising a material selected from the group consisting of zinc, zinc alloys, and combinations thereof.
16. The battery of claim 6, wherein the battery comprises an anode-less battery wherein zinc is deposited on Cu or carbon.
17. A method for improving the performance of a battery comprising a manganese-based cathode comprising: n+ Metal / metalloid ions of are introduced into the electrolyte, wherein M represents metal / metalloid and n is from about 2 to about 4.
18. The method of claim 17, wherein the metal / metalloid ion is selected from Ti 4+ 、TiO 2+ 、Ni 2+ , Fe 2+ , Fe 3+ ,La 3+ 、Zr 4+ 、ZrO 2+ Sn 2+ 、Bi 3+ 、V 4+ 、V 3+ 、V 2+ 、Al 3+ , Sb 3+ Mg 2+ , Ca 2+ , B 3+ and their combinations.
19. The method of claim 17, wherein the metal / metalloid ion is present in the form of a salt selected from the group consisting of TiOSO4, NiSO4, La(NO3)3, FeSO4, Fe2(SO4)3, H3BO3, MgSO4 and combinations thereof.
20. The method of claim 17, wherein the electrolyte comprises about 0.05% (w / v) to about 10% (w / v); or about 0.1% (w / v) to about 5% (w / v) of metal / metalloid ions.
21. The method of claim 17, wherein the battery is charged and discharged to form a metal / metalloid doped manganese-based cathode by in-situ doping of the metal / metalloid ions.